2016
DOI: 10.18410/jebmh/2016/247
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Awareness and Practices of Hand Washing Amongst Mothers of Under-Five Children in the Slums of Guwahati City

Abstract: INTRODUCTION Hand washing with soap at critical events reduces the incidence of diarrhoeal diseases by about 42% to 47% and respiratory infections by 30% which are important contributors of under-five child morbidity and mortality in India. The awareness and hand washing practices amongst mothers residing in poor environmental settings of slums are important as they are the primary caregivers and have a determining role in the health of their children. OBJECTIVES To assess the awareness, practices and factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…9 This study showed that HHPs of the mothers, main caregivers of the pediatric patients after the pediatric staff in pediatric wards, were mainly affected by age, education level, and the anxiety they experienced in the peroperative period. Limited studies about HH applications of mothers have shown that 65.3% of the mothers, in the study by Mech and Ojah, 10 and 96% of the mothers, in the study by Pati et al, 11 were aware about the importance of hand washing with soap for infection control. Jabbar et al reported that hand washing with soap and water was significantly more effective at removing C. difficile spores from the hands of volunteers than alcohol-based hand rubs.…”
Section: Discussionmentioning
confidence: 97%
“…9 This study showed that HHPs of the mothers, main caregivers of the pediatric patients after the pediatric staff in pediatric wards, were mainly affected by age, education level, and the anxiety they experienced in the peroperative period. Limited studies about HH applications of mothers have shown that 65.3% of the mothers, in the study by Mech and Ojah, 10 and 96% of the mothers, in the study by Pati et al, 11 were aware about the importance of hand washing with soap for infection control. Jabbar et al reported that hand washing with soap and water was significantly more effective at removing C. difficile spores from the hands of volunteers than alcohol-based hand rubs.…”
Section: Discussionmentioning
confidence: 97%
“…For many children, the attention of an adult can be a rewarding consequence, that is, social reinforcement (Wasik, Senn, Welch, & Cooper, 1969). Mech and Ojah (2016) study found that there was awareness among the mothers regarding the importance of hand washing in the prevention of diseases. This finding is in accord with the finding of this study as was stated from the interviews; "I tell her how to dust off, wash dishes…."…”
Section: Discussionmentioning
confidence: 99%
“…Andersen (2016) deliberated children as intergenerational environmental change agents in their family homes in Australia. Mech and Ojah (2016) in India assessed the awareness, practices and factors associated with hand washing amongst mothers. In Denmark, Grønhøj and Thøgersen conducted studies in 2012 and 2017 that examined proenvironmental behaviour on personal attitudes and family norms.…”
Section: Introductionmentioning
confidence: 99%
“…To pass on their ecological knowledge to the youth and raise awareness, parents or carers may use hands-on daily activities in combination with different approaches such as stories, proverbs, myths, folktales and rituals (AwuahNyamekye, 2014); shopping, cooking, cleaning and gardening (Kara, Aydos & Aydin, 2015: 46); hand washing (Mech & Ojah, 2016); green purchasing (Hài & Mai, 2013); recycling (Barr, Shaw, & Coles, 2011); water saving (Keramitsoglou & Tsagarakis, 2011) and family communication (Dyck, 2012). These approaches are used for the purposes of explaining to people -in particular children -the importance of the environment, and the need to protect and conserve it (Awuah-Nyamekye, 2014: 52).…”
Section: Environmental Campaignsmentioning
confidence: 99%